Prophylactic Low-Dose Paracetamol Administration for Ductal Closure and Amplitude-Integrated Electroencephalography in Preterm Infants - Schreiner, Christina; Sappler, Maria; Höck, Michaela; Hammerl, Marlene; Neubauer, Vera; Kiechl-Kohlendorfer, Ursula; Griesmaier, Elke (Frontiers in Pediatrics, 2022)
Introduction: Prophylactic low-dose paracetamol administration is used to induce closure of the ductus arteriosus in preterm infants. In our recent study we found no impairment on microstructural maturation processes in the brain of preterm infants at term-equivalent age following prophylactic low-dose paracetamol administration. We now assessed amplitude-integrated electroencephalography signals in preterm infants with and without exposure to prophylactic low-dose paracetamol administration. Methods: Infants <32 gestational weeks born between 10/2014 – 12/2018 received prophylactic paracetamol (10 mg/kg intravenously every eight hours until echocardiography after at least 72 hours) and form the paracetamol group; infants born between 02/2011 – 09/2014 formed the control group. Four single parameters (continuity, cyclicity, amplitude of lower border, bandwidth span) together with their sum (Burdjalov total score) and presence of sleep-wake cycles were compared between the groups. Results: Included in the study were 338 infants, of whom 217 received prophylactic paracetamol and 121 formed the control group. The paracetamol group showed a significantly higher number of sleep-wake cycles per hour and a significantly higher total scores compared to the control group (p<0.05). Conclusion: Paracetamol exposure in has been regarded critically with respect to safety in preterm infants in recent years. We found no impairment on amplitude-integrated electroencephalography signals in preterm infants receiving low-dose prophylactic paracetamol compared to controls. Growing awareness and greater availability of data may encourage the clinicians to administer prophylactic paracetamol for ductal closure in preterm infants. The clinical relevance of our findings has to be evaluated in long-term follow up studies on neurodevelopmental outcome.